Typical difficult situations in doctor-patient interactions - Asanova Азізе; Khaustova Олена (Psychosomatic Medicine and General Practice, 2018)
Every day a physician encounters complex situations in his practice and communicates with patients in various emotional and psychological conditions. In most cases, patients are forced to seek medical advice, not because they want it. Sometimes they attend a visit to hospital by an advice of a family member or friend. This review article presents typical recommendations for interaction with patients in different clinical situations.